Development and performance evaluation of packed bed solar drier for drying oyster mushroom, Pleurotus florida - Palaniselvam, V; Chinnanchetty, G; Venkatachalam, P; Kathirvel, K; Arumuganathan, T (Mushroom Research, 2015)
please see the full text